Flaky spinel cobalt ferrite as well as preparation method and application thereof

The preparation of sheet spinel cobalt ferrite by CO2 laser induction method solves the problem of unstable operating performance of SOFC at high temperatures, achieving higher electrochemical performance and lower preparation costs.

CN119873898AActive Publication Date: 2025-04-25BOHAI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411858500.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-25
Estimated Expiration
2044-12-17

Smart Images

  • Figure CN119873898A_ABST
    Figure CN119873898A_ABST
Patent Text Reader

Abstract

The invention provides flaky spinel cobalt ferrite as well as a preparation method and application thereof, and belongs to the technical field of solid oxide batteries. The preparation method comprises the following steps: dissolving a Co source and a Fe source in deionized water, adding citric acid, uniformly stirring, heating in a water bath until the solution becomes reddish brown transparent gel, drying, and grinding to obtain first powder; secondly, CO2 laser induction is conducted on the first powder twice in the air atmosphere with the laser power being x, and second powder is obtained; wherein x is more than 4W and less than or equal to 10W. And finally, washing and drying the second powder to obtain the spinel cobalt ferrite with the flaky morphology. Compared with common spinel cobalt ferrite, the flaky spinel cobalt ferrite is applied to the SOFC as a cathode material, so that the polarization impedance of the battery can be reduced by 0.023 ohm cm < 2 >, the maximum power density can be increased by 0.38 W cm <-2 >, and the oxygen reduction activity and stability of the SOFC can be improved. In addition, by adopting the CO2 laser induction method, the preparation process is simplified, the time cost is reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid oxide batteries, and in particular to a flaky spinel cobalt ferrite and a preparation method and application thereof. Background Art

[0002] Adhering to the development of sustainable materials and technologies is an important solution to today's energy and environmental problems, especially the contradiction between traditional fossil fuel energy and environmental protection. In the field of batteries, solid oxide fuel cells (SOFCs) inherit the high efficiency characteristics and all-solid-state structure of fuel cells. Compared with secondary batteries that require charging and discharging operations, SOFCs can directly convert chemical energy into electrical energy in an environmentally friendly way, and have therefore become one of the research hotspots. However, SOFCs usually need to operate at 800-1000°C. Long-term operation at high temperatures can easily cause the battery to coarsen particles and cause performance degradation. Some researchers have tried to lower the operating temperature and found that this adjustment will delay the oxygen reduction reaction (ORR) kinetics of the cathode, thereby reducing the overall efficiency of SOFC. Replacing the appropriate cathode material may effectively reduce the operating temperature of SOFC.

[0003] Perovskite oxide materials have high oxygen ion transport performance and fast surface oxygen exchange kinetics, and are therefore considered the most promising cathode candidate materials. However, the segregation effect of alkaline earth metals, large thermal expansion coefficients, and high costs hinder their application and development. Compared with perovskite-based cathodes, spinel materials generally do not contain alkaline earth metals, which effectively prevents the degradation of material properties due to the formation of carbonates during preparation and operation. In addition, spinel materials are currently often used as a protective layer for metal interconnects in SOFC stacks and have excellent stability. Therefore, using spinel materials as cathode materials may help improve the stability of SOFCs.

[0004] Spinel cobalt ferrite is one of the common spinel materials. At present, its common preparation methods are mainly coprecipitation, hydrothermal and sol-gel methods. The spinel morphology prepared is mostly irregular nanoparticles. These preparation methods are not only complicated, but also require high temperature and high pressure environment reaction, or sintering at high temperature (about 1000℃), which takes a long time to prepare and is costly. Long-term high-temperature calcination may also produce adverse chemical reactions, affecting product quality.

[0005] In summary, it is necessary to develop a flaky spinel cobalt ferrite and a preparation method and application thereof to solve the above problems. Summary of the invention

[0006] In view of the technical problems existing in the background technology, the present application provides a flaky spinel cobalt ferrite and its preparation method and application, aiming to solve the technical problem that the long-term operation performance of SOFC at high temperature is not stable enough by preparing suitable cathode materials. The present application adopts the CO2 laser induction method to prepare a flaky spinel cobalt ferrite (CoFe2O4), and adjusts the size and degree of fragmentation of the flaky morphology of the spinel CoFe2O4 by changing the laser power, so that it has a higher specific surface area. Compared with ordinary granular spinel CoFe2O4, the SOFC prepared by using the flaky spinel CoFe2O4 has better oxygen reduction activity, lower polarization impedance and higher maximum power density. In addition, the CO2 laser induction method simplifies the preparation process of spinel CoFe2O4, reduces time cost and improves production efficiency.

[0007] In a first aspect, the present application provides a method for preparing flaky spinel cobalt ferrite, which is prepared by a CO2 laser induction method, comprising the following steps:

[0008] S1, dissolving the Co source and the Fe source in deionized water, adding citric acid after sufficient stirring, and stirring evenly to obtain a precursor solution.

[0009] S2, heating the precursor solution obtained in step S1 in a water bath until it becomes a reddish brown transparent gel, and then drying and grinding the reddish brown transparent gel to obtain a first powder.

[0010] S3, evenly spread the first powder obtained in step S2, and perform CO2 laser induction twice in an air atmosphere to obtain a second powder. The power of the CO2 laser induction is x, and 4W<x≤10W.

[0011] S4, after the second powder obtained in step S3 is cooled to room temperature, the second powder is washed and dried to obtain the flaky spinel cobalt ferrite.

[0012] In some embodiments, in step S1, the concentration of the metal ions in the precursor solution is 0.1 mol / L; the molar ratio of the metal ions to the citric acid is 1:(1.2-1.5); further, the molar ratio of Co ions to Fe ions in the metal ions is 1:2.

[0013] In some embodiments, in step S3, the CO2 laser induced scanning speed is 100-150 mms -1 , the CO2 laser induced power is 6-8W.

[0014] In some embodiments, in step S1, the Co source is a cobalt salt, and the Fe source is an iron salt; further, the cobalt salt is cobalt nitrate, and the iron salt is iron nitrate.

[0015] In some embodiments, in step S2, the water bath heating temperature is 60-90°C.

[0016] In some embodiments, in step S2, the drying method is forced air drying; the forced air drying temperature is 70-90°C and the time is 10-12h.

[0017] In some embodiments, in step S4, the drying temperature is 70-90° C. and the drying time is 10-12 hours.

[0018] In some embodiments, in step S4, the washing refers to washing with distilled water for 2-3 times and then washing with ethanol for 2-3 times.

[0019] In a second aspect, an embodiment of the present application provides a flaky spinel cobalt ferrite, which is prepared by any preparation method in the aforementioned schemes, wherein the stoichiometric ratio of Co to Fe in the flaky spinel cobalt ferrite is 1:2; and the flaky spinel cobalt ferrite has a flaky morphology.

[0020] In a third aspect, an embodiment of the present application provides an application of flaky spinel cobalt ferrite, wherein the flaky spinel cobalt ferrite prepared in the aforementioned scheme is used as a cathode material for a solid oxide fuel cell.

[0021] The beneficial effects of this application are:

[0022] The present application provides a flaky spinel cobalt ferrite and its preparation method and application. The present application changes the morphology of the spinel cobalt ferrite by CO2 laser induction method, increases its specific surface area, and effectively improves the oxygen reduction activity of the flaky spinel cobalt ferrite, so that it exhibits excellent performance at 750-800°C. Compared with the traditional sol-gel preparation method, the use of CO2 laser induction can significantly shorten the time cost required to prepare cathode materials, simplify the preparation process, and improve production efficiency.

[0023] (1) The present application adopts a CO2 laser induction method to prepare flaky spinel cobalt ferrite. Compared with the slow and energy-consuming traditional high-temperature calcination method, this method has a simple preparation process, a fast reaction speed, and low energy consumption. By adjusting the CO2 laser power, the synthesized spinel cobalt ferrite can have a suitable flaky structure and improve the activity of the oxygen reduction reaction. Among them, the product prepared with a laser of 8W maintains a good nano-layer flaky shape, and the included nanoparticles are relatively small. The product as a whole presents a small and well-separated flaky morphology.

[0024] (2) The flake-shaped spinel cobalt ferrite has a higher specific surface area than the granular spinel cobalt ferrite prepared by high-temperature solid phase, which can provide a longer three-phase reaction interface and increase the surface active sites, making the flake-shaped spinel cobalt ferrite have better electrochemical properties. Compared with the performance of ordinary granular spinel cobalt ferrite, its polarization impedance at 750°C is reduced by 0.023Ωcm 2 , the maximum power density increased by 0.38 W cm -2 .

[0025] (3) CO2 laser induced preparation can reduce the number of sintering times and shorten the sintering time, avoiding adverse chemical reactions that may be caused by long-term high-temperature calcination, making the powder prepared by CO2 laser induced preparation more delicate and regular in morphology, without the need for grinding, further shortening the time for electrode preparation.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 The SEM images of the products prepared in Examples 1-3 and Comparative Examples 1-3 of the present application when magnified 6K times;

[0029] Figure 2 The SEM images of the products prepared in Examples 1-3 and Comparative Examples 1-3 of the present application when magnified 2K times;

[0030] Figure 3 XRD patterns of the products prepared in Examples 1-3 and Comparative Examples 1-3 of the present application;

[0031] Figure 4 Electrochemical impedance diagrams of symmetrical batteries CFO-4W-S, CFO-6W-S, CFO-8W-S and CFO-10W-S prepared for the application examples of this application at 750°C;

[0032] Figure 5 Electrochemical impedance diagram of the symmetrical battery CFO-SG-S prepared for the application example of this application at 750°C;

[0033] Figure 6 It is the relaxation time distribution diagram of the symmetrical batteries CFO-6W-S, CFO-8W-S, CFO-10W-S and CFO-SG-S prepared in the application example of this application at 750°C;

[0034] Figure 7 These are the electrochemical impedance diagrams of the symmetrical battery CFO-8W-S prepared in the application example of this application at 700°C and 800°C respectively;

[0035] Figure 8 This is a comparison chart of the output power of the full batteries CFO-6W-F, CFO-8W-F, CFO-10W-F and CFO-SG-F prepared in the application example of this application at 750°C;

[0036] Fig. 9 The output power diagram of the full battery CFO-8W-F prepared in the application example of this application at 700°C and 800°C respectively;

[0037] Fig.10 This is the O1s spectrum of the product prepared in Example 1-2 of the present application obtained by X-ray photoelectron spectroscopy (XPS) testing. DETAILED DESCRIPTION

[0038] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0040] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0042] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0043] SOFC usually needs to operate at 800-1000℃. Long-term operation at high temperature can easily cause the battery to coarsen particles, resulting in performance degradation. Using spinel materials as cathode materials may help improve the stability of SOFC. Spinel cobalt ferrite is one of the common spinel materials. Currently, its common preparation methods are mainly coprecipitation, hydrothermal and sol-gel methods. The prepared spinel morphology is mostly irregular nanoparticles. These preparation methods are not only complicated, but also require high temperature and high pressure environment reactions, or sintering at high temperature (about 1000℃). The preparation time is long and the cost is high. Long-term high-temperature calcination may also produce adverse chemical reactions, affecting product quality.

[0044] In order to solve the technical problem that the performance of SOFC is not stable enough under high temperature for a long time, the present application provides a flaky spinel cobalt ferrite and its preparation method and application. Among them, a flaky spinel cobalt ferrite (CoFe2O4) is prepared by CO2 laser induction method, which makes the preparation process simpler, shorter and cheaper; the size and degree of fragmentation of the flaky morphology of the spinel CoFe2O4 are adjusted by changing the laser power, so that it has a higher specific surface area, thereby increasing the electrochemical performance of the spinel CoFe2O4; by using the spinel CoFe2O4 as a cathode material in SOFC, the stability of the performance of SOFC in high temperature operation is improved.

[0045] In a first aspect, the present invention provides a method for preparing flaky spinel cobalt ferrite, comprising the following steps:

[0046] S1, dissolving the Co source and the Fe source in deionized water, adding citric acid after sufficient stirring, and stirring evenly to obtain a precursor solution.

[0047] In some embodiments, the concentration of metal ions in the precursor solution is 0.1 mol / L.

[0048] In some embodiments, the molar ratio of the metal ions to the citric acid is 1:(1.2-1.5). Further, the molar ratio of the Co ions to the Fe ions in the metal ions is 1:2.

[0049] The purpose of adding citric acid to the precursor solution is to make the Co ions and Fe ions better combine. The addition of citric acid can effectively control the morphological characteristics and particle size of the material, make its distribution more uniform, and reduce the occurrence of agglomeration. However, the amount of citric acid added should not exceed the above-defined molar ratio range. Too much citric acid will cause excessive combination of Co ions and Fe ions, thereby making the combination between some metal ions stronger and producing a second phase of impurities; too little citric acid will cause the material structure to be unstable, which is not conducive to the synthesis of the material.

[0050] In some embodiments, the Co source is a cobalt salt, and the Fe source is an iron salt; further, the cobalt salt is cobalt nitrate, and the iron salt is iron nitrate.

[0051] S2, heating the precursor solution obtained in step S1 in a water bath until it becomes a reddish brown transparent gel, and then drying and grinding the reddish brown transparent gel to obtain a first powder, which is the precursor powder.

[0052] In some embodiments, the water bath is heated at a temperature of 60-90° C. for a time of 15-25 h.

[0053] In some embodiments, the drying method is forced air drying, and the forced air drying temperature is 70-90° C. and the time is 10-12 hours.

[0054] S3, evenly spread the first powder obtained in step S2, and perform CO2 laser induction twice in an air atmosphere to obtain a second powder. The power of CO2 laser induction is x, and 4W<x≤10W. Further, the power of CO2 laser induction is 6-8W. Further, the power of CO2 laser induction is 8W.

[0055] The product prepared by CO2 laser induction method has a flaky morphology. The power of CO2 laser induction will affect the temperature at the moment of laser firing, and then affect the formation and final morphology of spinel cobalt ferrite. Specifically, first, flaky spinel cobalt ferrite cannot be prepared when the laser is 4W, and flaky spinel cobalt ferrite is successfully prepared when the laser is 6-10W. Second, as the laser power increases, the flaky morphology of the product is broken to varying degrees, so that a small amount of fine nanoparticles are mixed in the flaky morphology. Among them, the product prepared by the laser of 4-8W maintains a good nano-layer flaky shape, and the mixed nanoparticles are small. Specifically, the product prepared by the laser of 4-6W presents a large-scale adhesion flaky morphology, and the product prepared by the laser of 8W presents a small and well-separated flaky morphology. The flaky morphology of the product prepared by the laser of 10W is more broken, and there are more doped fine nanoparticles, and a small amount of agglomeration occurs.

[0056] In some embodiments, the CO2 laser induced scanning speed is 100-150 mms -1 .

[0057] S4, after the second powder obtained in step S3 is cooled to room temperature, the second powder is washed and dried to obtain flaky spinel cobalt ferrite, the chemical formula of the flaky spinel cobalt ferrite is CoFe2O4.

[0058] In some embodiments, the drying temperature is 70-90° C. and the drying time is 10-12 hours. Furthermore, the drying method is forced air drying.

[0059] In some embodiments, washing means washing with distilled water for 2-3 times, and then washing with ethanol for 2-3 times.

[0060] The flaky spinel cobalt ferrite powder prepared in the present application is relatively fine and does not require grinding, thereby effectively shortening the preparation time.

[0061] In a second aspect, an embodiment of the present application provides a flaky spinel cobalt ferrite having a flaky morphology and a stoichiometric ratio of Co to Fe of 1:2.

[0062] In a third aspect, the present application provides an application of a flaky spinel cobalt ferrite, including using the flaky spinel cobalt ferrite as a cathode material for SOFC. The SOFC prepared using the flaky spinel cobalt ferrite exhibits excellent performance at 750-800°C, and the oxygen reduction activity, polarization impedance and maximum power density are all higher than those of ordinary granular spinel cobalt ferrite.

[0063] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0064] Example 1

[0065] This embodiment provides a method for preparing flaky spinel cobalt ferrite, comprising the following steps:

[0066] S1, 0.873 g Co(NO3)2·6H2O and 2.424 g Fe(NO3)2·9H2O were dissolved in 30 mL deionized water at room temperature, and stirred on a magnetic stirrer until the mixture was clear and transparent. Then 2.836 g citric acid was added and stirred evenly to obtain a precursor solution.

[0067] S2, heating the precursor solution obtained in step S1 in a water bath at 60° C. for 20 h to obtain a reddish brown transparent gel, then placing the reddish brown transparent gel in an oven, drying it with air at 80° C. for 10 h, and then grinding it to obtain a first powder (i.e., precursor powder).

[0068] S3, the first powder obtained in step S2 is evenly spread, and the laser power is 8W and the scanning speed is 150mms -1 Under the conditions of , the first powder is subjected to CO2 laser induction twice in an air atmosphere to obtain a second powder.

[0069] S4, after the second powder obtained in step S3 is cooled to room temperature, the second powder is washed with distilled water for 2-3 times, and then washed with ethanol for 2-3 times, and then placed in an oven and dried by forced air at 80° C. for 10 hours to obtain a flaky spinel cobalt ferrite, which is named CFO-8W and has a chemical formula of CoFe2O4.

[0070] Example 2-3

[0071] The difference between Example 2 and Example 3 and Example 1 is that in step S3, the power of CO2 laser induction is changed to 6W and 10W respectively, and the other contents are substantially the same as Example 1 and will not be repeated here.

[0072] Comparative Example 1

[0073] Comparative Example 1 provides a method for preparing spinel cobalt ferrite by a sol-gel method, comprising the following steps:

[0074] S1, 0.873 g Co(NO3)2·6H2O and 2.424 g Fe(NO3)2·9H2O were dissolved in 30 mL deionized water at room temperature, and stirred on a magnetic stirrer until the mixture was clear and transparent. Then, 2.836 g citric acid and 3 g polyethylene glycol were added as a complexing agent and a combustion aid, respectively, to obtain a precursor solution.

[0075] S2, after adjusting the pH value of the precursor solution obtained in step S1 to 7 with ammonia water, the precursor solution is placed on a magnetic stirrer and stirred continuously for 30 minutes (room temperature), and then heated in a water bath at 60° C. for 20 hours to obtain CoFe2O4 gel.

[0076] S3, heating the CoFe2O4 gel obtained in step S2 at 600°C until it burns (i.e., pre-burning) to remove organic matter and moisture to obtain powder. Then, the pre-burned powder is pressed into a disc at a pressure of 15MPa, and the disc is sintered at 1000°C for 5 hours and ground to improve the uniformity and fineness of the particles to obtain spinel cobalt ferrite, which is recorded as CFO-SG.

[0077] Comparative Example 2

[0078] The difference between Comparative Example 2 and Example 1 is that the power of CO2 laser induction is changed to 4W in step S3, and the other contents are substantially the same as those in Example 1 and will not be repeated here. The product prepared in Comparative Example 2 is recorded as CFO-4W.

[0079] Comparative Example 3

[0080] The difference between Comparative Example 3 and Example 1 is that the amount of citric acid in step S1 is changed to 3.782 g, that is, the molar ratio of metal ions to citric acid in the precursor solution is changed to 1:2. The other contents are substantially the same as those in Example 1 and will not be described in detail here. The product prepared in Comparative Example 3 is recorded as CFO-8W 1:2 .

[0081] For ease of understanding, the differences between Examples 1-3 and Comparative Examples 1-3 are shown in the following table:

[0082]

[0083]

[0084] The morphology of the products prepared in Examples 1-3 and Comparative Examples 1-3 was characterized by scanning electron microscopy (SEM).

[0085] See also Figure 1 to Figure 2 As shown, Figure 1 The morphology of the products prepared in Examples 1-3 and Comparative Examples 1-3 when magnified 6K times, Figure 2The morphology of the products prepared by Examples 1-3 and Comparative Examples 1-3 when magnified 2K times. It can be seen that the morphology of the products prepared by the sol-gel method is in the form of particles of varying sizes, some of which are agglomerated, while the morphology of the products prepared by the CO2 laser induction method is in the form of flakes, and as the laser power increases, the flake morphology of the products is broken to varying degrees, so that a small amount of fine nanoparticles are mixed in the flake morphology. Among them, CFO-4W, CFO-6W and CFO-8W maintain good nano-layer flakes, and the mixed nanoparticles are relatively small. CFO-4W and CFO-6W present large-scale adhered flake morphologies, while CFO-8W is a small flake morphology with a good degree of separation. The flake morphology of CFO-10W is more broken, and it contains more fine nanoparticles. Figure 1 A small amount of agglomeration can be seen in the figure. This shows that the CO2 laser-induced preparation method will change the morphology of the material.

[0086] The structures of the products prepared in Examples 1-3 and Comparative Examples 1-3 were characterized by X-ray diffraction (XRD), and the following results were obtained: Figure 3 The X-ray diffraction pattern shown in the figure was analyzed by using Jade software to obtain the conclusion that Comparative Examples 2 and 3 failed to prepare flaky spinel cobalt ferrite, while Examples 1-3 and Comparative Example 1 successfully prepared flaky spinel cobalt ferrite. This shows that the laser power has an important influence on whether spinel cobalt ferrite can be successfully prepared and the morphological characteristics of the prepared spinel cobalt ferrite. In addition, according to the XRD spectrum of Comparative Example 3, it can be seen that excessive addition of citric acid leads to the appearance of impurities in the material, and thus spinel cobalt ferrite cannot be successfully prepared.

[0087] Application Examples

[0088] This application example includes the preparation of a symmetric cell and a full cell. The commercial anode-supported half-cell used in this application example was purchased from Zhongfu (Wuxi) New Energy Co., Ltd. In addition, CFO-4W, CFO-6W, CFO-8W, CFO-10W and CFO-SG were used as cathode materials, and a mixture of 92% pine alcohol and 8% ethyl cellulose was used as a binder.

[0089] The specific preparation steps of the symmetrical battery are as follows:

[0090] The cathode material and the binder are uniformly mixed to obtain a cathode slurry. Then, the cathode slurry is coated on the electrolyte BaZr 0.7 Ce 0.1 Y 0.1O3(BZCY) on both sides and sintered at 1000℃ for 2h to prepare symmetrical batteries, which were named CFO-4W-S, CFO-6W-S, CFO-8W-S, CFO-10W-S and CFO-SG-S respectively.

[0091] The specific preparation steps for the preparation of the full battery are as follows:

[0092] The cathode material and the binder were uniformly mixed to obtain cathode slurry. The prepared cathode slurry was applied to the electrolyte surface of the commercial anode-supported half-cell by screen printing and calcined at 1000°C for 2h to prepare full cells, which were respectively named CFO-6W-F, CFO-8W-F, CFO-10W-F and CFO-SG-F.

[0093] The electrochemical impedance spectroscopy of the symmetrical batteries CFO-4W-S, CFO-6W-S, CFO-8W-S, CFO-10W-S and CFO-SG-S prepared in the corresponding examples was tested at 750°C using an electrochemical workstation (Chenhua 660E) at 10 5 Up to 10 -1 The electrochemical impedance spectroscopy (EIS) data were collected and analyzed in the Hz range. The symmetrical cell was placed in a high-temperature tube furnace and the temperature was raised to 750°C in an air atmosphere for electrochemical impedance spectroscopy testing.

[0094] The polarization impedance data obtained from the test are shown in the table below.

[0095] project <![CDATA[Polarization impedance (Ωcm 2 )]]> CFO-4W-S 0.082 CFO-6W-S 0.054 CFO-8W-S 0.033 CFO-10W-S 0.067 CFO-SG-S 0.056

[0096] See also Figures 4 to 5 As shown in the figure, it is the electrochemical impedance diagram obtained by the test. Combined with the above table, it can be seen that with the increase of laser power, the polarization impedance of the symmetrical battery prepared by using flaky spinel cobalt ferrite shows a trend of first decreasing and then increasing, and the polarization impedance of CFO-8W-S and CFO-6W-S is smaller than that of CFO-SG-S, especially CFO-8W-S, whose polarization impedance is only 0.033Ωcm 2 . The polarization impedance of CFO-4W-S is the largest, and according to the XRD test results, it is not a flaky spinel cobalt ferrite structure, so there is no point in continuing the test. This shows that compared with ordinary granular spinel cobalt ferrite, the oxygen reduction reaction activity of the flaky spinel cobalt ferrite prepared by the CO2 laser induction method in this application is significantly increased, and the laser power is 8W as the optimal parameter. If the laser power is further increased to 10W, the oxygen reduction activity decreases instead.

[0097] The distribution relaxation time (DRT) method was used to analyze the electrochemical impedance spectra of CFO-6W-S, CFO-8W-S, CFO-10W-S and CFO-SG-S.

[0098] See also Figure 6 As shown in the figure, the relaxation time distribution diagrams of CFO-6W-S, CFO-8W-S, CFO-10W-S and CFO-SG-S are shown. It can be seen that the curves in the figure are divided into low frequency (LF), medium frequency (IF) and high frequency (HF) regions, which correspond to gas diffusion, oxygen molecule adsorption and dissociation, and charge transfer at the three-phase boundary (TPB), respectively, and the peak areas in the three regions are related to the polarization impedance values ​​in their corresponding frequency ranges. DRT analysis shows that compared with the other three symmetrical batteries, the area of ​​each peak of the relaxation time distribution curve of CFO-8W-S is the smallest, and the high-frequency and medium-frequency peaks are significantly reduced, indicating that the change in the morphology of spinel cobalt ferrite effectively promotes the charge transfer and adsorption and dissociation process of oxygen molecules in the oxygen reduction reaction (ORR). Among them, the promotion of the charge transfer process is due to the increase in the active sites of the material caused by the change in morphology, and the promotion of the adsorption and dissociation process of oxygen molecules is due to the increase in specific surface area caused by the change in morphology. Compared with CFO-SG-S, the high-frequency peaks of all materials prepared by laser methods are significantly reduced, and the medium-frequency peaks are also slightly reduced. The area of ​​the intermediate frequency peak of CFO-10W-S is not much different from that of CFO-SG-S, which proves that further increase of laser power has an adverse effect on the material morphology, resulting in a decrease in material performance.

[0099] The polarization impedance of CFO-8W-S at 700℃ and 800℃ was further tested, and the electrochemical impedance diagrams obtained were shown in Figure 7 The polarization impedance of CFO-8W-S at 700℃, 750℃ and 800℃ is 0.087Ωcm 2 , 0.033Ωcm 2 and 0.007Ωcm 2 .

[0100] The output power of the full batteries CFO-6W-F, CFO-8W-F, CFO-10W-F and CFO-SG-F prepared in the corresponding use cases was tested at 750°C, and the electrochemical impedance spectroscopy (EIS) data was collected and analyzed in the range of 105 to 10-1Hz using an electrochemical workstation (CHEN ZHHUA 660E). The full battery was placed in a high-temperature tube furnace, and air was used as an oxidant and H2 as a fuel to evaluate the output characteristics of the full battery at 750°C. The linear sweep voltammetry method was tested in the voltage range of 0-1.5V using an electrochemical workstation (Chenhua 660E). The maximum power density obtained from the test is shown in the table below.

[0101] project <![CDATA[Maximum power density (W cm -2 )]]> CFO-6W-F 0.63 CFO-8W-F 0.77 CFO-10W-F 0.45 CFO-SG-F 0.39

[0102] See also Figure 8As shown in the figure, it is the output power diagram of the full battery at 750°C. Combined with the above table, it can be seen that the power density of CFO-6W-F, CFO-8W-F and CFO-10W-F are all higher than that of CFO-SG-S. Among them, the maximum power density of CFO-8W-F is the highest, which is 0.77W cm -2 This indicates that the flaky spinel cobalt ferrite prepared by CO2 laser induction has better electrochemical properties, and the best laser power is 8W.

[0103] Further testing of the output power of CFO-8W-F at 700℃ and 800℃ yielded the maximum power density. Fig. 9 The maximum power density of CFO-8W-F at 700°C is 0.61 W cm -2 , the maximum power density at 800°C is 1.00 W cm -2 .

[0104] X-ray photoelectron spectroscopy (XPS) was performed on CFO-8W and CFO-6W prepared in Example 1-2. The O1s spectra obtained by analysis were shown in Fig.10 As shown. It can be seen that the peak at 529eV in the spectrum corresponds to lattice oxygen (O lat ), while the peak at 530 V corresponds to the adsorbed oxygen (O ads ). ads With O lat The ratio is usually used to express the relative oxygen vacancy content in different materials. ads / O lat The value is 1.05, CFO-8W O ads / O lat The value is 2.38, which means that within the power range of 6-8W, as the laser power increases, O ads / O lat The value gradually increases. This shows that the change of laser power can affect the oxygen vacancy concentration of the material. Oxygen vacancies are the active sites of electrochemical reactions. Therefore, cathode materials with higher oxygen vacancy concentrations have better ORR catalytic performance.

[0105] In summary, the present application provides a flaky spinel cobalt ferrite and its preparation method and application. A flaky spinel cobalt ferrite (CoFe2O4) is prepared by CO2 laser induction method, and an application of the CoFe2O4 spinel as a cathode material for preparing symmetrical batteries and full batteries is provided. The present application adjusts the size and degree of fragmentation of the flaky morphology of the CoFe2O4 spinel by changing the laser power. It can be seen from the SEM image that the CFO-8W prepared with a laser power of 8W has a small and well-separated flaky morphology, and the nanoparticles produced by the fragmentation are fewer, have a higher specific surface area, and exhibit excellent performance at 750-800°C. Compared with ordinary granular CoFe2O4 spinel, the flaky CoFe2O4 spinel prepared in the present application has better electrochemical properties when used as a cathode material due to the change in morphology, such as lower polarization impedance and higher maximum power density, as well as better oxygen reduction activity.

[0106] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing flaky spinel cobalt ferrite, characterized in that: The preparation is carried out by CO2 laser induction method, which includes the following steps: S1, dissolving the Co source and the Fe source in deionized water, stirring thoroughly, adding citric acid, and stirring evenly to obtain a precursor solution; S2, heating the precursor solution obtained in step S1 in a water bath until it becomes a reddish brown transparent gel, and then drying and grinding the reddish brown transparent gel to obtain a first powder; S3, evenly spread the first powder obtained in step S2, and perform CO2 laser induction twice in an air atmosphere to obtain a second powder; the power of the CO2 laser induction is x, and 4W<x≤10W; S4, after the second powder obtained in step S3 is cooled to room temperature, the second powder is washed and dried to obtain the flaky spinel cobalt ferrite.

2. The method for preparing flaky spinel cobalt ferrite according to claim 1, characterized in that: In step S1, the concentration of the metal ions in the precursor solution is 0.1 mol / L; the molar ratio of the metal ions to the citric acid is 1:(1.2-1.5); further, the molar ratio of Co ions to Fe ions in the metal ions is 1:

2.

3. The method for preparing flaky spinel cobalt ferrite according to claim 1, characterized in that: In step S3, the CO2 laser induced scanning speed is 100-150 mms -1 , the CO2 laser induced power is 6-8W.

4. The method for preparing flaky spinel cobalt ferrite according to claim 2, characterized in that: In step S1, the Co source is a cobalt salt, and the Fe source is an iron salt; further, the cobalt salt is cobalt nitrate, and the iron salt is iron nitrate.

5. The method for preparing flaky spinel cobalt ferrite according to claim 1, characterized in that: In step S2, the water bath is heated at a temperature of 60-90°C.

6. The method for preparing flaky spinel cobalt ferrite according to claim 5, characterized in that: In step S2, the drying method is air drying; the air drying temperature is 70-90°C and the time is 10-12h.

7. The method for preparing flaky spinel cobalt ferrite according to claim 1, characterized in that: In step S4, the drying temperature is 70-90° C. and the drying time is 10-12 hours.

8. The method for preparing flaky spinel cobalt ferrite according to claim 7, characterized in that: In step S4, the washing refers to washing with distilled water for 2-3 times and then washing with ethanol for 2-3 times.

9. A flaky spinel cobalt ferrite prepared by the method for preparing a flaky spinel cobalt ferrite according to any one of claims 1 to 8, characterized in that: The stoichiometric ratio of Co to Fe in the flaky spinel cobalt ferrite is 1:2; the flaky spinel cobalt ferrite has a flaky morphology.

10. A use of the flaky spinel cobalt ferrite according to claim 9, characterized in that: The flaky spinel cobalt ferrite is used as a cathode material for a solid oxide fuel cell.

Citation Information

Patent Citations

  • Polymer matrix composite with laser-induced metallization characteristic

    CN104672890A

  • Preparation method of spinel-type porous high entropy oxide material

    CN108821351A

  • Method for synthesizing hovenia acerba-shaped heterostructure electrocatalyst through CO2 laser induction and application

    CN118299575A

  • Nano anode material for Li-ion battery and its preparing process

    CN1391298A

  • Method for obtaining material for enzyme-free biosensor by laser-induced coprecipitation of metals from solution of mixture of their salts

    RU2805054C1